Impaired T-cell migration to the CNS under fingolimod and dimethyl fumarate. Issue 6 (November 2017) - Mathias, Amandine; Perriot, Sylvain; Canales, Mathieu; Blatti, Claudia; Gaubicher, Coline; Schluep, Myriam; Engelhardt, Britta; Du Pasquier, Renaud
Abstract : Objective: To evaluate the long-term effects of treatments used in MS on the T-cell trafficking profile. Methods: We enrolled 83 patients with MS under fingolimod (FTY), natalizumab (NTZ), dimethyl fumarate (DMF), or other disease-modifying treatments (DMTs). Blood was drawn before treatment onset and up to 36–48 months. The ex vivo expression of CNS-related integrins (α4β1 and αL subunit of LFA-1) and the gut-related integrin (α4β7) was assessed using flow cytometry on CD4 + and CD8 + T cells. The adhesion profiles of CD3 + T cells to specific integrin ligands (vascular cell adhesion molecule-1 [VCAM-1], intercellular adhesion molecule-1 [ICAM-1], and mucosal vascular addressin cell adhesion molecule-1 [MAdCAM-1]) were measured in vitro before and after 12 and 36–48 months. Results: NTZ decreased the frequency of α4β1 + and α4β7 + integrin expressing T cells and the binding of these cells to VCAM-1 and MAdCAM-1, respectively. After 12 months, DMF induced a decreased frequency of αL high CD4 + T cells combined with reduced binding to ICAM-1. By contrast, with FTY, there was a doubling of the frequency of α4β1 + and αL high, but a decreased frequency of α4β7 + T cells. Strikingly, the binding of α4β1 +, α4β7 +, and to a lesser extent of αL high T cells to VCAM-1, MAdCAM-1, and ICAM-1, respectively, was decreased at month 12 under FTY treatment. The presence of manganese partially restored the binding of these T cells to VCAM-1 in vitro, suggesting that FTY interferes with integrin activation. Conclusions: In addition to NTZ, DMF and FTY but not other tested DMTs may also decrease T-cell–mediated immune surveillance of the CNS. Whether this mechanism may contribute to the onset of CNS opportunistic infections remains to be shown.